Identification of Prednison and Methyl Prednisolon in Weight-Gain Jamu from Online Marketplace Using TLC-Densitometry Method - Fatmawati, Sofia; Siregar, Mirawati; Ananta, Lastri; Adjie, Sundari Kusuma (Universitas Muhammadiyah Kalimantan Timur, 2024)
Jamu or traditional medicine is an ingredient or mixture of ingredients derived from plant ingredients, animal ingredients, mineral ingredients, extract preparations (galenic), or a combination of these ingredients which have been used for generations for healing based on experience. Weight-gain jamu is a traditional medicine which is useful for increasing appetite and body weight. The product is widely used today and marketed through online platforms. This study aims to determine the corticosteroids Prednisone and Methyl Prednisolone that are present in weight-gain jamu using the TLC-Densitometry method. This study used 10 samples of weight-gain jamu purchased from the Shopee e-marketplace with inclusive criteria. Silica Gel GF 254 nm was used as the stationary phase. The mobile phases used are chloroform: ethyl acetate (1:9) for prednisone and water-saturated butanol: toluene: ether (5:10:85) for methyl prednisolone. Spiked samples were performed for confirmation of method validation. The results of this research showed that 2 jamu samples contained prednisone at 247 nm wavelength, and no jamu samples were positive for methyl prednisolone. This method could be applied to detect corticosteroids such as prednisone and methyl prednisolone in weight gain herbal medicine.